Case report: Perilymphatic fistula from a round window microfissure - Seo, Toru; Kemmochi, Arata; Koike, Yosuke; Aomi, Mizuho; Shinohe, Tatsuya; Komori, Manabu (Frontiers in Neurology, 2023)
A microfissure near the round window niche is an anatomical structure that communicates between middle ear and the ampulla of the posterior semicircular canal. It has been suggested that the microfissure can cause inner ear symptoms; however, the etiology has not yet been confirmed clinically. We report, to our knowledge, the first case of microfissure with complaint of hearing loss and vertigo and improvement in hearing after surgical sealing of the microfissure. A 50-year-old man complained of hearing disturbance, tinnitus with flowing-water sound in the left ear, and a floating sensation upon pushing the left tragus. He had moderate sensorineural hearing loss (43.3 dB) in the left ear for 3 days. His hearing worsened and he complained of severe vertigo. An exploratory tympanotomy was performed 8 days after onset. A microfissure and accumulation of clear fluid in the floor of the round window niche were detected, and leakage point was packed with connective tissue. One month after surgery, his hearing (20.0 dB) and disequilibrium had improved. The inner ear symptoms improved after the surgery in this case, suggesting that the microfissure might have caused the symptoms.